Civil War and Ideology Conflict as Seen in Alex Irvine’s Transformers: Exodus - Mutia Mutia; Edria Sandika (English Department, Faculty of Humanities, Andalas University, 2022)
This study discusses civil war and ideology conflict represented in Alex Irvine’s Transformers: Exodus. It aims to analyze how the ideological conflict contributes to civil war in the novel and the moral messages that the readers can learn from the narrative. Antonio Gramsci’s theory of hegemony and Terry Eagleton’s theory of ideological features are used to examine ideology’s role, and the moral-philosophical approach is used to analyze moral values. The findings suggest the existence of three ideologies: the Cybertronian traditions, the Autobots’ ideology, and the Decepticons’ ideology. In addition, this study finds that the novel contains moral values related to peace, toleration, and diplomacy.